Emergency braking performance of motorcycle riders: skill identification in a real-life perception-action task designed for training purposes - Rosalie, Simon; Huertas-Leyva, P.; Nugent, M.; Savino, G.; Pierini, M.; Baldanzini, N. (2019)
Collisions with other vehicles represent the biggest threat to riders of powered-two-wheeler (PTW), and while emergency braking is the evasive manoeuvre most frequently required in PTW riding, many riders fail to perform it adequately due to constraints on response time precipitated by failures of perception, cognition and control actions. Effective rider training methods are necessary for the development of braking proficiency in response to emergency situations. This study proposes a testing and training paradigm that exploits a closer similitude with the real-world scenario by maintaining the natural coupling of action (vehicle manoeuvring) and perception (higher order skill) that underlies any coordinated response to an emergency event. The aim of this study was to understand the behaviour of the riders in the execution of emergency braking coupled with visual perception of vehicle motion as a response to an imminent collision and determine parameters that can be used to identify differences in skill level. Participants performed emergency braking trials in a realistic and controlled scenario using a mock-up of an intersection conflict with a real car initiating a left turn manoeuvre across the path of a PTW approaching from the opposite direction (Left Turn Across Path/Opposite Directions). Analysis of the deceleration patterns recorded during 12 trials per participant revealed that performance of braking in response to an unpredicted moving hazard differs from that in a planned self-timed hard braking. In addition, our results indicate that PTW rider performance may be assessed in a reliable and objective way using the combination of vehicle kinematics and human performance measures. The study identified four categories of riders classified by their level skills. Finally, an important finding was the lack of correlation of both years of riding experience and self-assessed overall riding skill with an objective measure of emergency braking performance such as effective deceleration. The results of this study will support a new training approach and provide insights for future design of active safety systems.